2007
DOI: 10.1016/j.jmwh.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

How Breastfeeding Works

Abstract: Human milk is a complex secretion that is the sole ideal food for babies for at least the first 6 months of life. The amount and composition of the milk is largely independent of the mother's diet. The composition of the milk changes during lactogenesis II, and these changes can be used as biochemical markers of the onset of copious milk secretion. After 1 month of lactation, there are few further changes in the composition of milk until the volume of milk decreases substantially as the baby weans completely. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 47 publications
2
99
2
2
Order By: Relevance
“…The fat content of milk is also known to increase with the duration of breastfeeding in proportion to the emptying of the alveoli [86]. Thus, even if the storage capacity influences fat concentration in milk, it does not affect the total amount of fat consumed by the child [87]. While the concentration of lactose shows no significant change with stage of lactation, variations in milk glycans, e.g.…”
Section: Milk Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fat content of milk is also known to increase with the duration of breastfeeding in proportion to the emptying of the alveoli [86]. Thus, even if the storage capacity influences fat concentration in milk, it does not affect the total amount of fat consumed by the child [87]. While the concentration of lactose shows no significant change with stage of lactation, variations in milk glycans, e.g.…”
Section: Milk Compositionmentioning
confidence: 99%
“…Although PRL stimulates the synthesis of milk proteins, it does not control the amount of milk produced once lactation is established. In fact, the quantity of milk produced is correlated to the draining efficiency of the suckling and is accordingly upregulated if the breast is well-drained [87]. Moreover, the efficient draining of the breast appears to be more important than the frequency of feeding to stimulate milk production.…”
Section: Breastfeeding Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes affect the levels of these components and are dependent on the time of day and the milk maturation. Studies have reported that the nutritional and immunological properties of human milk are important to children and that they vary depending on the time of day as well as during the course of lactation (Kent 2007;França et al 2010França et al , 2013Honorio-França et al 2013). There is a relationship between the immunological and nutritional factors present in milk and the development of chronic diseases, including hypertension (Taylor et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding even reduces the incidence of acute illnesses and likely decreases the risk of a number of chronic diseases. Several studies have investigated the association of breastfeeding with a variety of chronic diseases, including diabetes (Davis, 2001;Kent, 2007). A reduced incidence of breast cancer is the most well documented long-term effect of breastfeeding on mothers and it has been shown to affect blood pressure, obesity/overweight and diabetes (Horta, 2007).…”
Section: The Effect Of Breastfeeding On Breast Cancer and Diabetesmentioning
confidence: 99%